Strategies in Building State Islamic University of North Sumatera’s Management Major Students’ Entrepreneurial Spirit - Nailul Muna; Zuhrinal M. Nawawi (International Journal Labs, 2022)
Entrepreneurship is a process of creativity and innovation activities in creating a change by taking advantage of existing opportunities and resources so that they can add value to the economy. Being an entrepreneur is very important and needs to be developed for students of the Management Study acara at the State Islamic University of North Sumatra. This writing is motivated by the high unemployment rate in Indonesia and the low employment opportunities in Indonesia which make students able to become entrepreneurs, so the employment opportunities will increase and economic growth in Indonesia will be more advanced. The purpose of this study is to show how the strategy in fostering the spirit and spirit of entrepreneurship in Management Study acara students at the State Islamic University of North Sumatra. In this study, the method used is a survey method with a sample of 20 students of Management Study acara at the State Islamic University of North Sumatra. The research analysis used is a descriptive analysis by conducting direct interviews.